Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fonc.2020.581321
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Axillary Lymph Node Status With a Nomogram Based on Breast Lesion Ultrasound Features: Performance in N1 Breast Cancer Patients

Abstract: Objective: To develop a nomogram for predicting axillary lymph node (ALN) metastases using the breast imaging reporting and data system (BI-RADS) ultrasound lexicon. Methods: A total of 703 patients from July 2015 to January 2018 were included in this study as a primary cohort for model construction. Moreover, 109 patients including 51 pathologically confirmed N1 patients (TNM staging) and 58 non-metastatic patients were recruited as an external validation cohort from March 2018 to August 2019. Ultrasound imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…At present, many studies evaluated the relationship between the axillary lymph node ultrasound characteristics and the properties of axillary lymph nodes. Some research reported that the L/S of axillary lymph nodes is of great significance for judging metastasis of axillary lymph nodes [ 12 , 13 ]. Some researchers believe that disappearance of lymph node hilum is helpful for judging metastasis of lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, many studies evaluated the relationship between the axillary lymph node ultrasound characteristics and the properties of axillary lymph nodes. Some research reported that the L/S of axillary lymph nodes is of great significance for judging metastasis of axillary lymph nodes [ 12 , 13 ]. Some researchers believe that disappearance of lymph node hilum is helpful for judging metastasis of lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Du et al [ 15 ] reported that the morphology and blood flow grading of axillary lymph nodes in ultrasound signs were independent influencing factors for predicting lymph node metastasis. Luo et al [ 12 ] constructed an ROC curve for predicting axillary lymph node status using ultrasound signs (lymph node size, lesion boundary). Its AUC reached 0.75 (95% CI: 0.70-0.79) and 0.91 (95% CI: 0.84-0.97), indicating a reliable predictive ability.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al (26) found that breast cancer with calcification had a higher rate of lymph node metastasis. Luo et al (27,28) found that the tumor pathological type, tumor burr sign, and calcification characteristics were related to axillary lymph node metastasis. These studies are consistent with the findings of the present study.…”
Section: Figurementioning
confidence: 99%
“…A multivariate analysis is performed in [ 40 ] to diagnose breast cancer to get the confidence interval of 95% of the area under the curve (AUC), which is shown for the primary cohort as 0.75 and 0.91 for the external cohort. This study achieved 88% sensitivity.…”
Section: Related Workmentioning
confidence: 99%